Cytokine Levels in Neural Pain in Leprosy - Angst, Débora Bartzen Moraes; Pinheiro, Roberta Olmo; Vieira, Joyce Soares da Silva; Cobas, Roberta Arnoldi; Hacker, Mariana de Andréa Vilas-Boas; Pitta, Izabela Jardim Rodrigues; Giesel, Louise Mara; Sarno, Euzenir Nunes; Jardim, Márcia Rodrigues (Frontiers in Immunology, 2020)
Pain is a frequent symptom in leprosy patients. It may be predominantly nociceptive, as in neuritis, or neuropathic, due to injury or nerve dysfunction. The differential diagnosis of these two forms of pain is a challenge in clinical practice, especially since they often coexist in the same patient. A better understanding of the cytokine profile may serve as a tool in assessing patients and also help comprehend the pathophysiology of leprosy pain. Patients with leprosy and neural pain (n=22), neuropathic pain (n=18), neuritis (nociceptive pain) (n=4), or without pain (n=17) as well as those with diabetic neuropathy and neuropathic pain (n=17) were recruited at the Souza Araujo Out-Patient Unit (Fiocruz, Rio de Janeiro, RJ, Brazil). Serum levels of IL1β, IL-6, IL-10, IL-17, TNF, CCL-2/MCP-1, IFN-γ, CXCL-10/IP-10, and TGF-β were evaluated in the different groups. Impairment in thermal or pain sensitivity was the most frequent clinical finding (95.5%) in leprosy neuropathy patients with and without pain, but less frequent in the diabetic group (88.2%). Previous reactional episodes occurred more often in patients in the leprosy and pain group (p = 0.027). Analysis of cytokine levels demonstrated that the concentrations of IL-1β, TNF, TGF-β, and IL-17 in the sera of patients with leprosy neuropathy with neuropathic or nociceptive pain were higher in comparison to the samples of leprosy neuropathy patients without pain. In addition, these cytokines levels were significantly augmented in leprosy patients with neuropathic pain in relation to those with neuropathic pain due to diabetes. IL-1β levels were an independent variable associated with both types of pain in patients with leprosy neuropathy. IL-6 concentration was elevated in both groups with pain. Moreover, CCL-2/MCP-1 and CXCL-10/IP-10 levels were higher in patients with diabetic neuropathy versus those with leprosy neuropathy. In summary, IL-1β was an independent variable related to neuropathic and nociceptive pain in patients with Hansen´s disease and might be an interesting biomarker for patient follow-up. IL-6 was higher in both groups with pain (Hansen’s disease and diabetic patients) and may be a therapeutic target in pain control.